2001
DOI: 10.1017/s1357321700002117
|View full text |Cite
|
Sign up to set email alerts
|

Pension Fund Valuations and Market Values

Abstract: The text of this paper, together with the abstract of the discussion held by the Institute of Actuaries on 25 October 1999, are printed in British Actuarial Journal, 6, I, 55-141.However, when this paper was discussed by the Faculty of Actuaries, the following ‘Survey of Practice’ had been carried out, and was also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Regulators then have to design a process regarding when trustees and firms need to take action and what action. Head et al (2001) suggested that trustees and members would not find it easy to accept the psychology of a target solvency ratio under 100%. So, with a starting point of the current solvency ratio, the regulator would also consider how far below 100% it is; the risks being taken, risk disclosures and risk margin (excess of buyout cost over liabilities); the employer covenant; and the solvency projected for the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regulators then have to design a process regarding when trustees and firms need to take action and what action. Head et al (2001) suggested that trustees and members would not find it easy to accept the psychology of a target solvency ratio under 100%. So, with a starting point of the current solvency ratio, the regulator would also consider how far below 100% it is; the risks being taken, risk disclosures and risk margin (excess of buyout cost over liabilities); the employer covenant; and the solvency projected for the future.…”
Section: Discussionmentioning
confidence: 99%
“…The discounted income valuation smoothed asset values when markets were volatile (Head et al, 2001). However, achieving this by constant parameters (income growth and discount rates) is questionable when economic conditions change, as Exley et al (1997) pointed out in relation to the assumptions hard-coded into the MFR requirements.…”
Section: Valuation Of Assetsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time as the theoretical developments, regulatory and consumer pressures constrained actuarial discretion in pensions and insurance (Needleman & Roff, 1995;Shelley et al, 2002) so that payouts from long-term funds were more mechanically linked to investment performance. There followed a series of papers applying option pricing theories (also called market-consistent valuation) to many areas of actuarial work: pensions (Exley et al, 1997;Head et al, 2000;Chapman et al, 2001), life insurance (Hare et al, 2000;Hibbert & Turnbull, 2003;Sheldon & Smith, 2004) and general insurance (Cumberworth et al, 2000;Dreksler et al, 2015).…”
Section: What a Difference 20 Years Makesmentioning
confidence: 99%
“…One actuarial method of determining the bonus is to begin with a calculation of a smoothed value of assets. Head et al (2000) provide a description of their development and justification in the context of DB funds. One common approach is for the value of shares to be determined by discounting future dividends at the actuarial valuation rate.…”
Section: Smoothed Bonusesmentioning
confidence: 99%